Identification of Agroindustry Spatial Distribution and Its Relationship with Regional Development in the Bandung Basin - Azizah, Zumrotul Nur; Fadila, Rizkiyah Amaliah; Mudzakir, Aditya Muhammad; Ramadhan, Muhammad Daiyan (Universitas Gorontalo, 2025)
This study aims to identify the spatial distribution patterns of agro-industries in the Bandung Basin Area and examine their correlation with regional development dynamics. The analytical methods used include the Composite Index, Weighted Overlay Analysis, Hotspot Getis-Ord Gi* Analysis, and Gamma Coefficient Correlation Analysis. The findings indicate that 28 percent of the Bandung Basin Area is suitable for agro-industrial development, primarily in West Bandung Regency and the eastern part of Bandung Regency, with significant correlation to regional development.